Toksisitas Isolat Lokal Bacillus thuringiensis (H-14) dan Isolat Sandi 18 Serta Lama Efektivitasnya di dalam Air terhadap Larva Nyamuk Anopheles dan Culex - Daniel Lantang; Rosye H.R. Tanjung (Jurusan Biologi FMIPA Universitas Cenderawasih, 2010)
The research of toxicity local isolate Bacillus thurigiensis (H-14) and 18 codeword isolate along the efectivity on the water concerning to the Culex and Anopheles. The research aim to acquainted about the toxicity of B. thuringiensis isolate H-14 local and 18 codeword isolate along of the toxicity on the water concerning to the Culex and Anopheles. The methode is laboratory experiment wich used complete randome, analysis the data to wich BNJ test and 0.05% confidence standart. The result shows that isolate of local B. huringiensis H-14 and coderword 18 toxic concerning to Culex and Anopheles B.thurngiensis H-14 0.06 ml concentrate, 0.08 ml concentrate and 0.1 of effective of the Anopheles death until 6 day, and 0.1 ml effective concentrate show the Culex death until 7 day.Isolate 18 in 0.08 concentrate and 0.1 effective of Culex until 5 day and 0.1 ml concentrate 0.1 ml effective of the Anopheles until 7 day. Analysis varians shows the different act control concentrate in the other side, the act of concentrate isnt different significant. Key words: Bacillus thuringiensis, Local isolate, toxicity, Anopheles and Culex larva.